Collapse of an empire lessons for modern Russia - Gaĭdar, E. T. (Egor Timurovich) (Brookings Institution Press, 2007)
"Uses world history, the Soviet experience, and economic analysis to demonstrate why Russian nostalgia for empire could lead to repeating past strategies that result in instability, leaving Russia vulnerable to economic downturns"--Provided by publisher.